Muda Berkarya Untuk Bumi: Gerakan Daur Ulang dan Sosialisasi Lingkungan di SMKN 1 Musuk - Ariyo Fajar Wibowo; Arneta Wahyu Prabawati; Apriani Eva Rahmasari; Ardian Zanuar Dwi Aji Prasetyo; Luki Sri Anggorowati (Pusat Riset dan Inovasi Nasional, 2025)
Maintaining cleanliness and preserving the environment is an obligation for everyone in this world, to keep our lives safe from diseases and disasters caused by human actions. However, in reality, many people still do not maintain cleanliness and do not preserve the environment. One way to maintain cleanliness and preserve the environment is through recycling or utilizing waste to create new products. The purpose of this community service is to remind and educate the students of SMK N 1 Musuk so that they are always attentive and sensitive to their surroundings, as well as able to use items or waste that are no longer needed to create new products with practical value. This community service uses a socialization method, which involves providing materials and practical assignments to the students of SMK N 1 Musuk. This socialization was conducted in class XI AKL 1. The result of this community service is that the students of SMK N 1 Musuk have a better understanding of how to utilize waste and trash around them into products or items that have new utility value. The students of SMK N 1 Musuk can also express their creative ideas through waste utilization, one example being making frames from cardboard and decorating them with waste. In addition, this socialization can also increase students' awareness to maintain school cleanliness and preserve the surrounding environment to help reduce pollution around us.